Abstract reasoning ability as measured by the Raven Progressive Matrices Test (1938) in various clinical syndromes - Du Toit, E. C. M.(Elizabeth Catharina Maria),1925- (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (D. Phil.) -- Universiteit van Pretoria, 1953.